Aspects of Place Meaning in Heritage Tourism (Case Study: Rumah Balai Ujung Tanjung, Tanjungbalai City, Indonesia) - Muhammad Habib Auliya; Nurlisa Ginting (Talenta Publisher, 2023)
Tourism is one of the industries that can improve the welfare of the people in an area, one.of.which is heritage.tourism. Visits to heritage tourism are one of the fastest growing tourist activities, so heritage tourism is an asset that should be developed by each region. In heritage tourism, there is a place attachment. Place attachment is a bond made by humans with a place. One aspect of the formation of place attachment is the meaning of place. A historical tourist attraction that has a place attachment is the Rumah Balai Ujung Tanjung Tanjungbalai. This study aims to analyze aspects of the meaning of the place owned by Rumah Balai. The.research.method used in this.research is a concurrent mixedmethod. The results of the analysis carried out stated that the aspect of the meaning of the place owned by Rumah Balai Ujung Tanjung is still low and this can be improved by increasing aspects of physical characteristics and aspects of social interaction. So that it can increase the number of visitors who come.